Systematic significance of antennal segmentation and sense cones in Thripidae (Thysanoptera: Terebrantia) - Zhang, Shimeng; Mound, Laurence A.; Feng, Jinian (Zootaxa, 2019)
Variation is discussed concerning the number of antennal segments in adults, and the number of their sense cones, among 182 of the 289 genera of Thripidae. Brief comments are also made concerning antennal structure and sensoria among the other seven terebrantian families. The plesiotypic condition for Thysanoptera is 9-segmented antennae, but fusion between various segments leads to a reduction in number to as few as five segments, and such fusion occurs in unrelated species. In Thripidae, antennal segment III never bears more than one sense cone, but the distribution of sense cones on segments IV–VIII varies and is tabulated. On antennal segment IV, species in nearly all Panchaetothripinae genera and more than half of Thripinae genera have two sense cones, but genera of Dendrothripinae and Sericothripinae bear only one on this segment. The differing patterns of segmental fusion that occur in Thripidae are discussed in association with the number of sense cones on VI–VIII; species with 7, 8 or 9 segmented antennae almost always lack a sense cone on the terminal segment. It is concluded that the number of antennal segments is subject to irregular homoplasy, and is thus sometimes an unreliable indicator of relationships.